Application of model-free adaptive temperature control in medium frequency induction heating. Issue 1 (1st February 2022) - Li, Demin; Qin, Qingliang; Yang, Xiaoqian
Abstract: Induction heating has a series of advantages such as high heating efficiency, low energy consumption, and environmental protection. It is widely used in the heat treatment of metal workpieces. Only when the temperature of heat treatment meets the process requirements can the quality of workpiece be guaranteed, so the temperature control algorithm is very important. The heat treatment requirements of thick wall pipeline are more stringent than those of conventional workpieces, in order to better control the heat treatment temperature, a model-free adaptive temperature control algorithm based on data-driven is proposed. The principle and rationality of the algorithm were analyzed, and the previous process data were analyzed and fitted. Then the controller was designed and tested in the field of thick-wall pipe heat treatment. The results show that this method can improve the accuracy of temperature control, enhance the uniformity of temperature distribution, and meet the requirements of the production process.